Polymer Grafting and its chemical reactions - Purohit, Priyank; Bhatt, Akanksha; Mittal, Ravi K.; Abdellattif, Magda H.; Farghaly, Thoraya A. (Frontiers in Bioengineering and Biotechnology, 2023)
Polymer grafting is a technique to improve the morphology, chemical, and physical properties with significant improvement. This technique has the potential to improve the existing conduction and properties of polymers other than charge transport; as a result, it might be more related to solubility, nano-dimensional morphology, biocompatibility, bio-communication, and so on. A polymer's physicochemical properties can be modified even further by creating a copolymer with another polymer or by grafting. There are three general methods for synthesizing graft copolymers are 'grafting too, grafting from, and grafting through. In summary, the 'grafting to' procedure entails attaching pre-polymerized chains to backbone polymers with reactive end-groups through the chemical reaction. Here the various chemical approaches for polymer grafting, like free radical, click reaction, amide formation, and alkylation process importance is covered comprehensively. The modification of polymers through reactions like FRP, RDRP, and REX is the most efficient because of their flexibility in working with distinct chemical groups and tolerance to impurities. The use of click chemistries has been developed in polymer science to produce macromolecular materials with specific properties for a variety of uses. As more and more reactions are discovered, click chemistry's scope expands. Cu-azide-alkyne cycloaddition and strain-promoted alkyne-azide cycloaddition (SPAAC) have been widely researched for uses, new research has concentrated on other 1,3-dipolar cycloadditions that also meet the click chemistry specifications. The present review covers all the pharmaceutical importance of the graft approaches and most of the reactions involved, however here the effectiveness of the graft-to approach is also defined, which is mainly dependent on the coupling chemistry used, the behavior of the chain side, and the length of the chain.